Implementasi Ekstrakurikuler Jumat Aktif dalam Mengembangkan Pendidikan Agama Islam di Pondok Pesantren Irsyadul Islamiyah Tanjung Medan - Hasibuan, Asril Azhari; Arsyad, Junaidi (EduInovasi: Journal of Basic Educational Studies, 2024)
This research was motivated by the desire of the boarding school to develop Islamic religious education through active Friday extracurricular activities, such as reciting the Qur'an, al-barzanji, Friday sermons and nasyid. The purpose of this study is to describe how the planning, implementation, evaluation and results of the implementation of active Friday extracurricular activities in developing Islamic religious education. This research uses a qualitative approach with descriptive analysis. Data sources or informants are school principals, supervising teachers, students and parents of students. The data collection techniques were carried out through observation, interviews and documentation. The results of this study reveal that 1) This active Friday extracurricular activity can develop Islamic religious education. This active Friday extracurricular activity can develop Islamic religious education, this can be seen from a deep understanding of the teachings of Islam, forming a deep understanding of the teachings of Islam. understanding of the teachings of Islam, forming the character of students in accordance with the values of Islam and the involvement of students in community activities. values of Islam and the involvement of students in community activities, 2) increasing the development of Islamic religious education apart from the active Friday extracurricular activity program, this activity must be supported by the attention and policies of the school principal, such as providing good facilities, building the character of students according to Islamic values and the involvement of students in community activities. school principal such as providing good facilities, and also a supervising teacher who is an expert in the Friday extracurricular activity program. in the active Friday extracurricular activity program. While the obstacle is the ability of students to vary in understanding the extracurricular material taught at the boarding school. taught at the boarding school